2012
DOI: 10.1371/journal.pone.0046226
|View full text |Cite
|
Sign up to set email alerts
|

Living with Cat and Dog Increases Vaginal Colonization with E. coli in Pregnant Women

Abstract: Background: Furred pets in the household are known reservoirs for pathogenic bacteria, but it is not known if transmission of bacteria between pet and owner leads to significantly increased rate of infections. We studied whether cats and dogs living in the household of pregnant women affect the commensal vaginal flora, and furthermore the need for oral antibiotics and rate of urinary tract infections during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 27 publications
1
12
2
Order By: Relevance
“…Pet exposure was also significantly associated with reduced Enterobacteriaceae among infants born vaginally without IAP but not exclusively breastfed afterwards. While our findings appear to contradict reports of greater Escherichia coli colonization in the vaginal microbiome of pregnant women who own pets [51], the timing of microbial changes in the developmental trajectory of infant microbiota is important to consider. Following vaginal delivery, Proteobacteria (especially Enterobacteriaceae ) are dominant within 3 months after birth, while Bacteroidetes and Firmicutes become more prevalent as the gut microbiota matures towards an adult-like profile [52].…”
Section: Discussioncontrasting
confidence: 98%
“…Pet exposure was also significantly associated with reduced Enterobacteriaceae among infants born vaginally without IAP but not exclusively breastfed afterwards. While our findings appear to contradict reports of greater Escherichia coli colonization in the vaginal microbiome of pregnant women who own pets [51], the timing of microbial changes in the developmental trajectory of infant microbiota is important to consider. Following vaginal delivery, Proteobacteria (especially Enterobacteriaceae ) are dominant within 3 months after birth, while Bacteroidetes and Firmicutes become more prevalent as the gut microbiota matures towards an adult-like profile [52].…”
Section: Discussioncontrasting
confidence: 98%
“…Our previous work has indicated differences in the microbiome of dust from homes with and without pets [33]. Stokholm et al [34] reported that in a cohort of 668 pregnant Danish women (COP-SAC), those who had a cat or dog in the home during pregnancy had increased Escherichia coli colonization in their vaginal flora compared with women with neither animal. Further, having a dog in the home during pregnancy is highly correlated with having a dog in the home during the child's few first years of life.…”
Section: Discussionmentioning
confidence: 98%
“…[(33)] Stokholm et al reported that in a cohort of 668 pregnant Danish women (COPSAC), those who had a cat or dog in the home during pregnancy had increased Escherichia coli colonization in their vaginal flora compared with women with neither animal. [(34)] Further, having a dog in the home during pregnancy is highly correlated with having a dog in the home during the child’s few first years of life. Any deficiencies in the child’s acquired microbiome due to a maternal vaginal or gut microbiome that has been altered by medication, may be subsequently and rapidly overcome by this very early exposure to a dog in the home environment.…”
Section: Discussionmentioning
confidence: 99%
“…Whether these associations can be attributed to changes in the infant gut microbiota remains to be seen. Sharing of specific microbes between pet and owner has been occasionally reported in adults [30-32], but colonization of the infant gut has rarely been studied in relation to pets. Using targeted methods to identify specific organisms, it has been reported that the presence of household pets does not influence colonization by Lactobacillus , E. coli , or C. difficile [23,33,34].…”
Section: Discussionmentioning
confidence: 99%